Pengaruh Jintan Hitam (Nigella sativa) Terhadap Sindrom Metabolik Pada Wanita Menopause - Diwanti Aulia Hasanah; Sutarto; Putu Ristyaning Ayu; Selvi Rahmawati (Medula, 2019)
Menopause is permanently cessation of menstruation for at least 12 months in women with a median age of 51 years. The incidence of chronic diseases will be increased in menopause women, so that it affects their quality of life. Changes in estrogen levels during menopause are associated with an increase in body fat. This is an alarm sign for women's health because it causes an increase in blood pressure, insulin resistance and dyslipidemia. These changes can contribute to an increased risk of metabolic syndrome in menopausal women. Black cumin plant is a spice plant belonging to the Ranunculaceae family and grows in various regions of the world. Black cumin seeds and oils are usually used as traditional medicine for various diseases. The main bioactive substance in black cumin, thymoquinone, has a major influence in improving metabolic syndrome in menopausal women, especially in controlling lipid and blood sugar profiles. The mechanism of hypolipidemic action of N. sativa based on research caused by an increase in the regulation of LDL molecules through receptor-mediated endocytosis, and several other mechanisms. The hypoglycemic effect of N. sativa is by maintaining the integrity of pancreatic β cells, causing an increase in insulin levels.